Analysis of Evidence Discrepancies in Employee Spending Audit Procedures at ABC University by KAP LMR - Dwi Puspita, Tasya; R. Sjarief Hidajat (Universitas Indo Global Mandiri Palembang, 2024)
This study investigates the audit of employee expenditures at ABC University, focusing on lecturer certification allowances. A qualitative method with a descriptive analysis approach was used to identify discrepancies between computer data archives (ADK) and payment orders (SPM). The results reveal discrepancies in the amounts reported in ADK and SPM concerning the lecturer certification allowances at ABC University. Although not materially significant, these findings indicate potential risks to the university’s internal control over financial administration. Verification with the university confirmed that administrative errors were the primary issue, highlighting the need to enhance audit procedures to improve financial reporting accuracy and strengthen internal control systems. This study underscores the necessity for improved audit procedures to enhance financial reporting accuracy and fortify internal control systems. The findings contribute to understanding and recommending improvements in financial management practices within higher education institutions, aiming to enhance transparency and accountability in university financial management.